Pengembangan Bahan Ajar Bahasa Arab Untuk Madrasah Ibtidaiyah - F, Fitriani; Hamzah, Andi Abdul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to provide a comprehensive explanation related to the development of Arabic language teaching materials that are in accordance with the needs of students at Madrasah Ibtidaiyah. To obtain the results of this study, the researcher used a qualitative research type using a literature review approach. The results of the study indicate that the teaching materials developed based on contextual and interactive are able to increase students learning motivation and understanding of Arabic. Validation from material and media experts shows that these teaching materials are very suitable for use, with a high average score. The implementation of teaching materials in the classroom also shows positive results on students ability to understand vocabulary, grammer, and Arabic language skills as a whole. This study recommends the integration of these teacing materials more widely in the learning process of Madrasah Ibtidaiyah to support the improvement of the quality and achievement of Arabic language, further research is recommended to explore the integration of digital technology in teaching materials for more interactive learning.